THE DIGITAL NATIVE STUDENTS’ PREFERENCE IN USING NEWSELA AS THE MEDIA OF DIGITAL LITERACY TO ENRICH STUDENTS VOCABULARY - Ikrar Genidal Riadil; Farid Romadhon (Asosiasi dosen IDEBAHASA KEPRI, 2020)
Digital Natives students born into an era of instant networking. It makes everything have a connection with technologies. Digital natives having sophisticated technology knowledge and skills that can be potentially harnessed for better learning engagement inside the classroom. As a follow-up to the issuance of Permendikbud Number 23 of 2015 concerning the Growth Movement of Budi Pekerti, in 2017, the government began to vigorously increase the literacy culture in schools through the “Gerakan Literasi Sekolah” (GLS). Teachers should be able to set an example in creating a spirit of literacy culture in school. Through the increasing reading culture for students, this also increases vocabulary for students in learning English. The Newsela application can help the teachers also the students to add references to enrich science as a provision for learning. This research aimed to distinguish the usage of Newsela as the media of literacy to enrich student’s vocabulary. This research pursued to answer two research questions; (1) is Newsela helps students to improve their reading ability? And (2) what are the impacts of Newsela application on the student’s on developing vocabulary? The Steps that the researchers used were; first, the researchers shared the questionnaire to the English students. Second, the researchers evaluated the responses from the respondents. Third, the researchers found out the answer about the impacts of Newsela to the students. This research used descriptive qualitative to conduct this research. This result of the research showed that Newsela helped students to improve their reading ability.